Environmental Quality and Life Satisfaction: Subjective Versus Objective Measures of Air Quality - Liao, Pei-shan; Shaw, Daigee; Lin, Yih-ming (Social indicators research, 2015)
The purpose of this paper is to investigate the influence of objective air quality on individual life satisfaction (LS) through the moderating effect of perceived air quality on the latter. Unlike previous studies, we incorporates both of the data from the 2010 Taiwan Social Change Survey and the monthly mean of Pollutant Standards Index (PSI) from fixed air quality monitoring stations to understand their association with individual well-being. A two-stage estimation approach is employed, in which individual perceived subjective air quality level is employed as an explanatory variable in LS regression models. The results show that the objective measure of air quality, PSI, is significantly associated with the perceived air quality and with LS, respectively. When the endogeneity of perceived air quality is considered in the relationship between objective air quality and life satisfaction, the results indicate that the perceived air quality has a positive influence on LS, while the effect of objective measure of air quality on the latter becomes insignificant. In sum, the objective air quality has an indirect effect, but no direct effect, on LS. Furthermore, individual's age, gender, health, and variables of environmental experience and behaviors are found to be significant determinants of LS. Discussions on the findings are provided.